(untitled) (Observatorio Económico, 2009)
A preexisting condition is the most galling circumstance a member of an Isapre (one of Chile’s private health insurers) has to face. Anyone who has one can neither enter nor leave these institutions. But it need not be that way. Every risk, including health risk, can be priced at its fair value. It is time, therefore, to start thinking about how to make private health care genuinely and seriously more competitive. Continue reading...